The Impact of Digital Political Polarization on Social Stability in Urban Communities After the 2024 General Elections - Haqqi, Halifa (Jurnal Ar Ro'is Mandalika (Armada), 2025)
This study investigates the impact of digital political polarization on social stability in urban communities following the 2024 General Elections. With the rise of digital platforms, political discourse has become increasingly fragmented, fostering polarized views among the electorate. This polarization has the potential to influence social stability, particularly in urban settings where diverse political opinions converge. By employing a mixed-methods approach, the research analyzes public sentiment through social media trends, surveys, and in-depth interviews. It explores how digital political polarization affects community interactions, public trust, and social cohesion. The findings suggest that while digital polarization can intensify political divides, it also presents opportunities for dialogue and collective problem-solving, depending on how urban communities manage digital engagement. The study highlights the need for effective media literacy and digital communication strategies to mitigate the adverse effects of polarization on social stability in post-election contexts.